O espírito japonês : esboço para uma arqueologia etnográfica do Ki 守 破 離 – Shuhari – Os três momentos do aprendizado da maestria - Lourenção, Gil Vicente Nagai (Universidade Federal de São Carlos, 2016)
In my Master's research, I evaluated the Japanese Kendō practice as a Japaneseness device, i.e., something that sought to "make Japanese". In this manufacturing process, Kendō focused on three connected planes: the 'Spirit' [Ki], the Sword and the Body. While development of the foregoing, this doctoral thesis sought to analyze data from life stories of Kendō practitioners and Documents about the notion of Ki – Life Force, Vital Energy – through an extensive ethnographic research in Brazil and Japan. The notion of Ki introduced itself as an important way to understanding the Japanese Culture itself, in a close relationship with an idiosyncratic notion of Love - Ai. The result was a theoretical and analytical potentiality to understand the Japanese Kinship and Japanese-and-Non-Japanese’s Family Studies, including cultural recognition processes whose assessment was made by anthropological and comparative perspectives
The japanese spirit : draft for an archeological ethnography of Ki
Keywords: Antropologia social; Parentesco; Cultura Japonesa; Ki-Energia; Transnacionalismo; Social anthropology; Kinship; Japanese culture; Ki-Energy; Ai-Love; Transnationalism; Japaneseness; CIENCIAS HUMANAS::ANTROPOLOGIA